Empowering Teachers through Lifelong Learning: Entrepreneurial Competence and Career Guidance in Albania - Blerina Dhrami (European Scientific Journal, ESJ, 2026)
In contemporary education systems, teachers are increasingly expected to contribute to students’ career development through entrepreneurship education and transversal competence formation. This paper examines the role of teacher lifelong learning and entrepreneurial competence in supporting career guidance processes in Albania, a context characterized by labor-market uncertainty and ongoing educational reform.The study adopts a mixed-method approach, combining policy and document analysis with quantitative data collected through an Erasmus+ project involving teachers, students, and business representatives. Descriptive statistical analysis is used to explore teachers’ self-perceived entrepreneurial competencies, participation in lifelong learning, and engagement in career-related support for students.The findings indicate that teachers report relatively high levels of entrepreneurial competence and demonstrate strong commitment to lifelong learning. However, structural gaps persist between policy objectives and educational practice, including limited formal preparation for career guidance, fragmented professional development opportunities, and uneven institutional support. As a result, teachers often perform career guidance functions informally and without systematic coordination.The paper concludes that teacher development represents a critical but underutilized component of career guidance systems. Strengthening lifelong learning frameworks and embedding entrepreneurial competence within teacher education can significantly enhance career guidance capacity. The Albanian case offers transferable insights for education systems seeking to align entrepreneurship education, teacher development, and career guidance in response to changing labour-market demands.